Synthetic shuttlecock dynamics - Loh, Zhi Han (Nanyang Technological University, 2022)
Badminton was initially a sport developed in the mid-19th century under the name of “battledore and shuttlecock”, and while its exact origins are unknown to date, games involving the use of shuttlecocks have been enjoyed by Eurasians for centuries [1]. Shuttlecocks are mainly divided into two types, based on the material they are manufactured from, naturally feathered and synthetic. The Badminton World Federation (BWF) is the authority in charge of grading and recognising shuttlecocks based on factors of aerodynamics, durability, and consistency. However, as technology improves, so too can the testing methods that BWF conducts on shuttlecocks, with innovative criteria introduced with the aim of improving gameplay. The objective of this Final Year Project (FYP) is to explore the correlation of a shuttlecock’s skirt deformation with its performance. Furthermore, chemically treated shuttlecocks which were found to have better durability (from past FYP) were added into this project. In this experiment, a total of 8 shuttlecocks with varying levels of performance, 4 of which are BWF competition graded, 2 non-competition graded and 2 chemically treated, will be tested, and compared. The complete list of shuttlecocks tested are listed below [2]: 1) RSL Classic Tourney – BWF Competition Graded 2) Li Ning A+300 - BWF Competition Graded 3) Yonex Aerosensa AS50 - BWF Competition Graded 4) Aeroplane EG1130 - BWF Competition Graded 5) Victor Gold No.1 – Non-Competition Graded 6) Ashaway Official - Non-Competition Graded 7) Type A Chemically Treated 8) Type C Chemically Treated The BWF Accredited Laboratory conducts shuttlecock testing through hiring professional international players, where three shuttlecocks are chosen at random from the same tube and smashed ten times. Each smash was recorded while ensuring that there is no permanent deformity or impairment of the shuttlecock within the span of the ten hits. Likewise, a specially designed experimental jig was used to consistently reproduce the smashing of a badminton racket. Each individual hit was recorded with a high-speed camera and evaluated using a Motion Tracking software for analysis. P value testing using a significance value of 5% was conducted to support the results. From the results, it can be concluded that the Chemically Treated shuttlecocks have lower maximum skirt deformations compared to the Non-Competition Graded shuttlecocks. Chemically Treated shuttlecocks produce similar deformation results as those of BWF Competition Graded shuttlecocks. This acts as a good indication of the shuttlecock skirt deformation criteria being used as a method of testing in the BWF Competition Grade approval. No significant differences were found between the BWF Competition Grade and Chemically Treated shuttlecocks.